Freeze-thaw and shore platform development in Gaspé, Québec - Trenhaile, A.; Rudakas, P. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1981)
The role of freeze-thaw action in coastal environments, with particular reference to the formation of sub-horizontal shore platforms in Gaspé, Québec, was investigated experimentally. Rock cores and crushed rock samples were subjected to: two freeze-thaw cycles of twelve and twenty-four hour durations; fresh water and three artificial sea water solutions of about half, one and a half, and 'normal' salinity; and two drainage conditions representing rock pools and vertical well drained surfaces. These variables were selected to simulate some of the local environments which exist between the cliff top and low tide level in coastal Gaspé. Shales were the most susceptible to frost breakdown, followed in turn by argillites, calcisiltites and dolomitic silty argillites, and graywackes. Greatest disintegration tended to be associated with sea water solutions of about half-normal salinity. The data suggest that breakdown is greatest in the lower portions of the cliff. Freeze-thaw may produce the moat-like pools commonly found at the back of shore platforms. Although the process undoubtedly facilitates wave erosion of the platform and cliff, however, there is no evidence to suggest that it causes shore platforms to assume subhorizontal gradients.